PENGARUH KEBERSIHAN,LINGKUNGAN KERJA TERHADAP KEJADIAN TB PADA PETUGAS KESEHATAN - Cory Febrina; Aldri Frinaldi; Dasman Lanin; Rembrandt Rembrandt; Genius Umar; Yulkifli Yulkifli; Nurhasan Syah; Imelda Rahmayunia Kartika; Fitrianola Rezkik; Rina Mariyana; Mesi Yunia Sari; Meladina Meladina; Cici Aprilliani; Kiki Amelia; Fanny Yuliana Batubara; Rindi Genesa Hatika; Washilla Audia; Abdi Iswahyudi Yasril; Juli Hendrita (Ensiklopedia of Journal, 2026)
Many cases of disease in healthcare workers are suspected to be related to environmental conditions, but the relationship between these two factors has not been clearly described. This study conducted a literature review regarding the influence of environmental conditions on occupational diseases in healthcare workers. Relevant articles were searched through electronic databases such as PubMed, ProQuest, Google Scholar, and Springer, with publications spanning the last 5 years. The search used the English-language keywords: "Hospital Environmental Hygiene, Occupational Health, and Tuberculosis". The inclusion criteria for articles were: (1) full access available, (2) English language, (3) type of research and observation, and (4) primary focus on hospital room temperature and occupational health of healthcare workers. The selection process and presentation of results followed the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) scheme. Results: Of the 1033 articles found, 8 research articles met the requirements and were in accordance with the research objectives for analysis. Conclusion: Work environment conditions play an important role in the emergence of tuberculosis (TB) in healthcare workers. Strengthening environmental controls and organizational support are crucial to protecting healthcare workers from occupational TB risks and ensuring a safer healthcare system.Keywords: Hospital Environmental Hygiene, Healthcare Worker Occupational Health, and Tuberculosis (TB).